Spatial Navigation Is Distinctively Impaired in Persistent Postural Perceptual Dizziness - Breinbauer, Hayo A.; Contreras, Maria Daniela; Lira, Juan P.; Guevara, Claudia; Castillo, Leslie; Ruëdlinger, Katherine; Muñoz, Daniel; Delano, Paul H. (Frontiers in Neurology, 2020)
Objective: To determine whether performance in a virtual spatial navigational task is poorer in persistent postural perceptual dizziness (PPPD) patients than in healthy volunteers and patients suffering other vestibular disorders. Methods: Subjects were asked to perform three virtual Morris water maze spatial navigational tasks: (i) with a visible target, (ii) then with an invisible target and a fixed starting position, and finally (iii) with an invisible target and random initial position. Data were analyzed using the cumulative search error (CSE) index. Results: While all subjects performed equally well with a visible target, the patients with PPPD (n=19) performed poorer (p<0.004) in the invisible target/navigationally demanding tasks (CSE median of 8) than did the healthy controls (n=18; CSE: 3) and vestibular controls (n=19; CSE: 4). Navigational performance in the most challenging setting allowed us to discriminate PPPD patients from controls with an area under the receiver operating characteristic curve of 0.83 (sensitivity 78.1%; specificity 83.3%). PPPD patients manifested more chaotic and disorganized search strategies, with more dispersion in the navigational pool than those of the non-PPPD groups (standard distance deviation of 0.97 versus 0.46 in vestibular controls and 0.20 in healthy controls; p<0.001). Conclusions: While all patients suffering a vestibular disorder had poorer navigational abilities than healthy controls did, patients with PPPD showed the worst performance, to the point that this variable allowed the discrimination of PPPD from non-PPPD patients. This distinct impairment in spatial navigation abilities offers new insights into PPPD pathophysiology and may also represent a new biomarker for diagnosing this entity.